1972
DOI: 10.1159/000122112
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Alpha- and Beta-Adrenergic Blocking Agents on the Increase in Renin Secretion Produced by Stimulation of the Renal Nerves

Abstract: The effect of α-adrenergic, β-adrenergic, and combined blockade on the increase in plasma renin activity produced by renal nerve stimulation was studied in dogs. Prior treatment with the blocking agent propranolol abolished this response. In dogs given phenoxybenzamine, blood pressure fell and plasma renin activity rose, but in dogs given propranolol as well as phenoxybenzamine the same depressor response was observed without a rise in plasma renin activity. Stimulation of the renal nerves in dogs treated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
0
1

Year Published

1973
1973
1999
1999

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(36 citation statements)
references
References 7 publications
2
33
0
1
Order By: Relevance
“…This reduction supports the hypothesis that a significant portion of vasodilatory drug-induced renin release is mediated by the beta-adrenergic component of the sympathetic nervous system. This interpretation is consistent with that of Loeffler and his associates (16) who have shown that direct stimulation of renal nerves in anesthetized dogs causes renin release and that this response can be blocked with propranolol. An increase in circulating catecholamines can also contribute to renin release by a betaadrenergic mechanism (6), and this effect would likewise be blocked by propranolol.…”
Section: Discussionsupporting
confidence: 92%
“…This reduction supports the hypothesis that a significant portion of vasodilatory drug-induced renin release is mediated by the beta-adrenergic component of the sympathetic nervous system. This interpretation is consistent with that of Loeffler and his associates (16) who have shown that direct stimulation of renal nerves in anesthetized dogs causes renin release and that this response can be blocked with propranolol. An increase in circulating catecholamines can also contribute to renin release by a betaadrenergic mechanism (6), and this effect would likewise be blocked by propranolol.…”
Section: Discussionsupporting
confidence: 92%
“…8 The kidney contains both ␣-and ␤-adrenoreceptors that respond to sympathetic stimulation with increased renin secretion. 9 Hypertension in several animal models, including the spontaneously hypertensive rat (SHR), is believed to be related to increased adrenergic activity. 10,11 Increased activity of both splanchnic and renal nerves has been reported in SHR versus normotensive Wistar-Kyoto control rats.…”
mentioning
confidence: 99%
“…* 0 - 81 In fact, studies of renal cortical slices indicate that a-adrenergic receptor stimulation of the juxtaglomerular cell with methoxamine does not increase renin release. * 4 The present investigation suggests that the marked increase in renin release with methoxamine is mediated via stimulation of the vascular ai-adrenergic receptor. The present results further suggest that this vascular a^receptor mechanism is stimulated only with marked reduction in renal blood flow.…”
Section: *"mentioning
confidence: 50%